„Homo novus" między młotem reklamy a kowadłem krytyki. Przypadek „Alberta, wójta krakowskiego" - Przybysz, Iwona (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article presents the analysis of the press reception of the drama Albert, wójt Krakowski by Stanisław Gabriel Kozłowski as well as the methods of creating Kozłowski’s image as the winner of the drama contest in memory of Wojciech Bogusławski in Warsaw. The dynamics of changes of the overall view on the drama, from almost instant acceptance to equally-fast dismissal of it by the literary critics may be perceived as a tool for diagnosing the literary hierarchy and the relationship between authors of award-winning texts, the reviewers and the juries. This analysis might also help to present the influence that the knowledge about the success of a text in a contest has on its critical perception.